Peningkatan Resiliensi pada Penyintas Kekerasan terhadap Perempuan Berbasis Terapi Kelompok Pendukung - Yudi Kurniawan; N. Noviza (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2017)
Abstract: This study aims to increase resilience among survivors of violence against women through support group therapy. As resilience increases, survivors of violence against women form a powerless community of women as a vehicle for victims of violence to share experiences. This research is important because the number of violence against women shows an increasing trend from year to year. The hypothesis in this study is that there are differences in resilience of survivors of violence against women in experimental group and control group after group therapy. Subjects in this study were 10 women victims of violence aged between 35-40 years at Seruni Kota Semarang Integrated Service Center and divided into experimental groups and control groups. The measuring tool used is Modified Connor-Davidson Resilience Scale. Modules were taken from the therapy groups of Brabender, Smolar, and Fallon supporters (2004). The study used quasi experiment with non-randomized pretest-posttest control group design. Data were analyzed using different test of independent sample t-test. The result of the research shows that there is difference of resilience scores of survivors against women in experimental group and control group with p = 0,001 (p 0,05). In conclusion, support group therapy is effective to increase resilience to survivors of violence against women.Abstrak: Penelitian ini bertujuan meningkatkan resiliensi pada penyintas kekerasan terhadap perempuan melalui terapi kelompok pendukung. Setelah resiliensi meningkat, penyintas kekerasan terhadap perempuan membentuk komunitas perempuan berdaya sebagai wadah korban kekerasan untuk berbagi pengalaman. Penelitian ini penting karena jumlah kekerasan terhadap perempuan menunjukkan tren peningkatan dari tahun ke tahun. Hipotesis dalam penelitian ini adalah ada perbedaan resiliensi penyintas kekerasan terhadap perempuan pada kelompok eksperimen dan kelompok kontrol setelah diberikan terapi kelompok pendukung.Subjek dalam penelitian ini adalah 10 perempuan korban kekerasan berusia antara 35-40 tahun di Pusat Pelayanan Terpadu Seruni Kota Semarang dan dibagi ke dalam kelompok eksperimen dan kelompok kontrol. Alat ukur yang digunakan adalah Modified Connor-Davidson Resilience Scale. Modul diambil dari terapi kelompok pendukung (Brabender, Smolar, Fallon, 2004). Penelitian menggunakan quasi experiment dengan non randomized pretest-posttest control group design. Data dianalisis menggunakan uji bedaindependent sample t-test. Hasil penelitian menunjukkan bahwa ada perbedaan skor resiliensi penyintas kekerasan terhadap perempuan kelompok eksperimen dan kelompok kontrol dengan p=0,001 (p0,05). Kesimpulannya, terapi kelompok pendukung efektif untuk meningkatkan resiliensi pada penyintas kekerasan terhadap perempuan.